Species diversity of pests of the suborder of shield bugs (Heteroptera) in agrocenoses of the Lazarevsky district of Sochi, Krasnodar Territory, Russia - E. V. Kashutina; L. N. Bugaeva; T. N. Ignatieva (Юг России: экология, развитие)
Aim. The aim of the work was to study the species diversity of pests of the suborder of shield bugs (Heteroptera) in agrocenoses of the Lazarevsky district of Sochi.This paper presents data on the distribution, abundance and density of Heptoptera pest populations in this location. Heteroptera were gathered twice a month during the growing season (April to October) and weekly in the autumn‐winter period (November to March). The choice of registration date during the growing season was determined by the appearance of the first phytophagous individuals after wintering. Identification of the identified phytophages was carried out in the laboratories of the station according to generally accepted methods.The paper presents data on the distribution, abundance and density of pest populations of the suborder of shield bugs (Heteroptera) in the Lazarevsky district of Sochi, Krasnodar Territory. As a result of this research, the species composition of the most common species of bedbugs in this area has been revealed. The most harmful species noted were: berry shield Dolycoris baccarum Linnaeus, 1758; ornate shield Eurydema ornata Linnaeus, 1758; Green shield Nezara viridula Linnaeus, 1758; ruled shield Graphosoma lineatum Linnaeus, 1758; brown‐marbled bug Halyomorpha halys Stål, 1855; oak lace‐maker Corythucha arcuata Say, 1832; sycamore lace‐maker Corythucha ciliata Say; pear lace‐maker Stephanitis pyri Fabricius and linden bug Oxycarenus lavaterae Fabricius, 1787.As a result of the research undertaken, an increase in the total number of bedbug populations, an expansion of trophic connections, an increase in aggressiveness and a change in the status of individual pest species were revealed.